Makna Simbolik Wayang sebagai Seni Spiritual dalam Ruwatan Murwakala - Ersnathan Budi Prasetyo (Institut Seni Indonesia Surakarta, 2007)
A puppet for Javanese people (man who knows the real) is a guidance of live. Itâ€™s arranges Javanese people how must they act to another, how could they realizing as human being and how should they relationship with the creator (God). Puppet consists a symbolic meaning from art language character or the myth. The tradition of ruwatan ceremony still used by Javanese people as a way to liberation and holies the sin that can catch the mischance in their life. In puppet story with title Murwokolo act on Central Java ruwatan ceremony, at the beginning estimated grew from Java ancient story. The story consist holies which is liberation the God and Goddess sinner to become holy again. Meruwat means prevent the sadness by showed ceremony which performing puppet Murwokolo act. People who must be get ruwatan ceremony called sukerta child or ma , according to bibliography Pakem Ruwatan Murwa Kala and other source that copied by Purwadi (2005) which is Serat Centhini (Sri Paku Buwana V). There was 60 calamity causes. Keyword: Puppet, Ruwatan, MurwokoloÂ